PENERAPAN APLIKASI SIMPEG BERBASIS E-GOVERNMENT DALAM PENGELOLAAN DATA INFORMASI KEPEGAWAIAN (Studi pada Badan Kepegawaian Daerah, Pendidikan dan Pelatihan Kota Bnjarmasin) - normajatun normajatun; Sayuti Enggok; Iswiayi Rahayu (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The existence of staffing management information systems in an institution is to facilitate thefilling or updating of staffing information data quickly, this can facilitate the process ofincreasing the rank of employees. assist the leadership in determining the employee who ismutated and promoted his position. Therefore, the purpose of this research is to find out theapplication of the Staffing Management Information System Application at the RegionalStaffing, Education and Training Agency of Banjarmasin City which is analyzed using threeelements of successful e-government development. The study used a qualitative descriptiveapproach.The data was collected by conducting interviews with three informants. The resultsof the study showed that from the support element can be known to have been agreed on thee-government framework both by the leadership and subordinates, has been allocatedfinancial human resources, time, and information, the availability of infrastructure in the formof computer networks, servers, internet networks, computers, computers, superstructures,namely legal institutions, and applications Staffing management information systems havebeen socialized to all employees. From the capacity element, it can be known that theavailability of financial resources is still lacking, technological infrastructure has not reached50% but existing human resources are already compete.